Writing The Research Background And Research Problem In The Research Report: A Content Analysis - Mustain Mustain (DIDAKTIKA, 2017)
This research aim at describing, evaluating, and classfiying the writing of background of the study and the quality of research problem on the bachelor students’ research report. This research is content analysis through Qualitative approach. The setting of this research was done for eight weeks in the college of teacher training and education, and the subjects was the bachelor degree of the students of English Department that they had submitted and publised their research report to the library. The data from observation, Indept-interview, and observation were analyzed through description the writing of the research background and the quality of research problem based on the theory adopted from Latief, then the research evaluate the quality, the next is classified to draw conclusion in the form of naration. The research showed that the use of English language in writing the research background of the students’ research report were enough, although those were still some weaknesses and far expected, such as Quantitative research that focuses on the theory-verifying, and Qualitative research which focuses on the theory-generating, and classroom action research discusses about problem-solving. The finding of the quality of research problems that had been collected, identified, classified, and described in term of the language aspect were enough, variable, research design, and hypothesis report aspects were also identified. In contrast, those research problem was found there were some techniques term used. For instance, the word of influence, effect, correlation, relationship, or and the research problem or question exposed the teaching and learning process without finding the information behind the data.